Ida : a sword among lions : Ida B. Wells and the campaign against lynching - Giddings, Paula (New York, N.Y. : Amistad, 2008)
Traces the life and legacy of the nineteenth-century activist and pioneer, documenting her birth into slavery, her career as a journalist and a pioneer for civil rights and suffrage, and her determination to counter lynching.
Holly Springs -- The new city and the ladies' car -- A breath of life, a winter of discontent -- Love and trouble -- A race in my arms -- City of the three murdered men -- Exodus -- "The truth about lynching" -- The loveliest lynchee was our Lord -- Light from a human torch -- St. Joan and Old Man Eloquent -- Exile no more -- "Let us confer together" -- Undivided duty -- Mobocracy in America -- Bull in the china shop -- Chicago and the wizard -- Calls -- Smoldering bridges -- The ladies' band -- The Alpha Suffrage Club -- Unsafe for democracy -- Known race agitator -- Prisoners of war -- Unfriendly takeovers -- The price of liberty.
Includes bibliographical references and index.
Keywords: Wells-Barnett, Ida B., -- 1862-1931.; African American women -- Biography; African American women civil rights workers -- Biography; African American women social reformers -- Biography; Lynching; Civil rights -- United States -- Biography; Journalists -- United States -- Biography; Lynching -- United States -- History; United States -- Race relations